Pemberian Diet Diabetes Melitus B1 terhadap Pasien Diabetes Melitus tipe 2, Post Coronary Artery Bypass Graft, Sternal Wound Dehiscence Radius Sternum, Post Wound Debridement Re-debridement, Anemia: Sebuah Laporan Kasus - Qizza Salsabila; Farapti Farapti (Universitas Airlangga, 2024)
Background: The Standardized Nutritional Care Process (NCP) in this case provide a B1 diabetes mellitus diet. DM B1 diet (2100 kcal) is a diet given to patients with diabetes mellitus with high protein requirements to meet daily needs and accelerate healing of infections due to chest wounds, in addition to controlling blood sugar to normal, increasing hemoglobin and albumin levels so that patients do not experience anemia and control body woight to be stable. Objectives: To determine the provision of standardized nutritional care including assessment, nutritional diagnosis, nutritional intervention, monitoring and evaluation of nutrition in patients with a medical diagnosis of type 2 diabetes mellitus on insulin, post coronary artery bypass graft, sternal wound dehiscence radius sternum, post wound debridement and re-debridement, with a diet in the form of a 2100 kcal B1 diabetes mellitus diet. Methods: Case studies were taken directly or primary data in October 2023 with inpatients at the Cardiac Medical Inpatient Installation of Surabaya Regional General Hospital. Results: NCP is carried out by providing nutritional interventions for DM B1 diet and monitoring and evaluation for 3 days. The fulfillment of patient intake is on average, 80-110% fulfilled even more, and only protein macronutrients are still in the deficit category. The DM diet is given with the 3J principle (right schedule, amount, type). The results of monitoring and evaluation of patients including overweight, hemoglobin improved on the third day and albumin was still in low levels, physical/clinical patients such as blood pressure, respiratory rate, pulse, SpO2, showed that they were normal, had mild pain and compos mentis consciousness. The patient's complaints of nausea, vomiting, liquid stools, shortness of breath were not found during the nutritional care process so that the patient was in a fairly good condition. Conclusions: The patient is in fairly good condition, appetite is not a problem, hemoglobin is improving, albumin is in the low category, BMI is in the overweight category, and physically / clinically good, so the healing process quickly improves and the target intake is met, only monitoring needs to be done on protein macronutrients.